DNA damage in arctic seabirds: baseline, sensitivity to a genotoxic stressor and association to organohalogen contaminants - Ane, Haarr; Ketil, Hylland; Norith, Eckbo; Gabrielsen, Geir Wing; Herzke, Dorte; Bustnes, Jan Ove; Blévin, Pierre; Chastel, Olivier; Moe, Borge; Hanssen, Sveinn Are; SAGERUP, Kjetil; Katrine, Borgå (Environmental Toxicology and Chemistry, 2018)
International audience Environmental contaminants are found throughout Arctic marine ecosystems, and their presence in seabirds has been associated with toxicological responses. However, there are few studies of genotoxicity in Arctic avian wildlife. The purpose of the present study was to quantify DNA damage in lymphocytes of selected seabird species and to examine whether accumulation of organohalogen contaminants ( OHCs) affects DNA damage. Blood was sampled from common eider (Somateria mollissima), black guillemot (Cepphus grylle), black-legged kittiwake (Rissa tridactyla), glaucous gull (Larus hyperboreus), arctic skua (Stercorarius parasiticus), and great skua (Stercorarius skua) in Kongsfjorden, Svalbard.Contaminant concentrations found in the six species differed presumably due to foraging ecology and biomagnification. Despite large differences in contaminant concentrations, ranging from ΣOHCs 3.3 ng/g ww in the common eider to ΣOHCs 895 ng/g ww in the great skua, there was no strong difference among the species in baseline DNA damage or sensitivity to a genotoxic stressor (i.e. hydrogen peroxide). Baseline levels of DNA damage were low, with median values ranging from 1.7% in the common eider to 8.6% in the great skua. There were no associations between DNA damage and contaminants in the investigated species, suggesting that contaminant concentrations in Kongsfjorden are too low to evoke genotoxic effects, or possibly that lymphocytes are resistant to strand breakage. Clearly, genotoxicity is a topic for future studies of Arctic seabirds